Experimental Study On Mechanical Strength And Performance Of Gigantochloa Ligulata Bamboo (Buluh Mata Rusa) Joints - Sham, Muhammad Harisfarhan Mohd (Universiti Sains Malaysia, 2022)
Bamboo has become a fairly common building material because of its originality, architectural qualities, and attractiveness. Bamboo is widely regarded as one of the most important non-timber forest resources due to the considerable socioeconomic benefits of products made from the material. Even though the bamboo contributes many benefits to the construction, there haven't been many studies examining the relationship between joints' compatibility and their mechanical behaviour. As a response, this study makes an investigation on the mechanical strength and performance of bamboo joints from the species Gigantocholoa Ligulata. The type of bamboo joint used in this study is column to beam and beam to beam section of orthogonal joint with various type of connections which is dowel, rope and dowel, bolt and nut, anchor bolt and fish mouth connection. The test used on the samples to get maximum load and deflection is static load test. All of the process in sample preparation and testing was done carefully to ensure the accuracy of the data. Based on the result, the fish mouth connection gives the best joint performance with the highest maximum load. The observed failure modes of the joint samples were the splitting, shear out, buckling and bolt bending.